A Case Study: Involuntary Planned Displacement. An Approach to the Restitution of Livelihoods in the Involuntary Resettlement of Arenal, Tilarán, Guanacaste, Costa Rica - Ávila Vargas, Gabriela (Revista Geográfica de América Central., 2022)
Costa Rica developed the Arenal hydroelectric megaproject in the 1970s to solve an energy problem. The proposed designs involved the involuntary displacement of 2,500 people. The Arenal community with the highest population density was analyzed. In the programs offered at the resettlement site, the objective was to identify the capital assets reached and their effect to counteract the risk of the population’s impoverishment. A qualitative analysis of secondary sources was conducted, and experts were interviewed. Over time, the resettled population (325 families) managed to recover their livelihoods by 83.11%, highly offsetting the risks of impoverishment. Recovering the economy and stabilizing it took time. They tried to replicate various agricultural models without success. However, based on the programs provided during the resettlement, from 1990 onwards, they carried out economic activities linked to tourism in a sustained manner that allowed them stability.